2020
DOI: 10.1002/slct.201903534
|View full text |Cite
|
Sign up to set email alerts
|

N‐Arylcyanothioformamides: Preparation Methods and Application in the Synthesis of Bioactive Molecules

Abstract: This comprehensive review discusses the various preparation methods of N‐arylcyanothioformamides and highlights the diverse chemistry and application of such reagents in organic synthesis since they were first reported. Specifically, the review describes applications of the preceding reagents in the preparation of the highly bioactive heterocyclic imidazolidineiminothiones, bis‐imidazolidineiminothiones and derivatives thereof. The review also demonstrates how N‐arylcyanothioformamides provide access to the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…At the outset of our work, we were interested in preparing 5-imino-1,3-diphenyl-2-thioxoimidazolidin-4-ones and 5-imino-1,3-diphenyl-2-selenoxoimidazolidin-4-ones as an extension to our previous work. 31,32 We attempted a previously reported procedure where Papadopoulos prepared N -phenylcyanoformamide by reacting phenyl isocyanate with potassium cyanide in water (Scheme 3). 33 The arylcyanoformamide product was only characterized by melting point.…”
Section: Resultsmentioning
confidence: 99%
“…At the outset of our work, we were interested in preparing 5-imino-1,3-diphenyl-2-thioxoimidazolidin-4-ones and 5-imino-1,3-diphenyl-2-selenoxoimidazolidin-4-ones as an extension to our previous work. 31,32 We attempted a previously reported procedure where Papadopoulos prepared N -phenylcyanoformamide by reacting phenyl isocyanate with potassium cyanide in water (Scheme 3). 33 The arylcyanoformamide product was only characterized by melting point.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are several methods in the literature for the synthesis of 1,3,4-thiadiazoles as described earlier, there are no reliable protocols to prepare 5-arylimino-1,3,4-thiadiazoles and sporadic examples of these species have been reported as minor or side products. A literature search has shown that isothiocyanates [ 21 ] or N -arycyanothioformamides [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] could in principle serve as potential starting materials and sources of sulfur. However, although the former (RN=C=S) has been reported to produce 5-arylimino-1,3,4-thiadiazoles under reflux conditions (61 °C) and long reaction times (10–12 h) [ 21 ], in our hands, the same reaction failed to produce any products and the isothiocyanates remained unreactive at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor, antiviral, antibacterial and antifungal properties of imidazolidineiminothiones and their derivatives have been systematically established over the past recent years [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. While the 1-position contains a carbonyl (C=O) group flanked by two nitrogen atoms ( N 1 and N 3 ), the heterocyclic ring contains adjoining imino and thione functional groups in the 4 and 5 locations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor, antiviral, antibacterial and antifungal properties of imidazolidineiminothiones and their derivatives have been systematically established over the past recent years [64][65][66][67][68][69][70].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%